Meningkatkan Kualitas Belajar Anak Didik Dalam Memahami Kandungan Surah Al-Humazah Kelas II Di MIS Nurul Hikmah AFD VI Tinjowan I - Sari, Sri Wulan; Alfiansyah, Muhammad; Amalia, Rizka; Nurfadillah, Annisa (Jurnal Tarbiyah dan Ilmu Keguruan Borneo, 2023)
This study describes several ways to improve the quality of students in understanding the content of surah al-Humazah in class II at MIS Nurul Hikmah. The type of research used in this paper is descriptive qualitative. Then for the data collection technique used by using interviews and also accompanied by various sources of reading literature from books and from various journals related to this discussion. The results of this study indicate that there are several ways that can be done to improve the learning quality of students in understanding the content of surah al-Humazah in class II MIS Nurul Hikmah, namely: 1) Provide an understanding of sura al-Humazah and then recite it regularly before learning begins, 2) Using supportive learning media, 3) The teacher must have creativity in teaching and dealing with the attitudes and behavior of class II MI students so that the teaching and learning process runs smoothly. As for the obstacles in efforts to improve the quality of students in understanding the content of surah al-Humazah in class II MI, namely the lack of concentration of students in the learning process, inadequate learning media, and the lack of teacher ability in teaching.